Peran Kepala Sekolah Dalam Melaksanakan Supervisi Untuk Meningkatkan Kompetensi Guru - Sry Hartati; Alhadi Yan Putra; Rohana Rohana (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2026)
This study aims to describe and analyze the role, constraints, and solutions of the principal in implementing supervision to improve teacher competency at SD Negeri 6 Banyuasin I. The method used is a descriptive qualitative approach with data collection techniques through in-depth interviews, observation, and documentation. The results of the study indicate that the principal plays a strategic role in improving teacher competency through planned, continuous, and collaborative supervision, not only as administrative control but also as professional development that involves identifying teacher needs, providing constructive feedback, and designing follow-up actions such as training or reflection. The implementation of supervision often faces obstacles in the form of time constraints due to administrative burdens, limited competence of the principal in reflective and constructive supervision, and limited supporting facilities and infrastructure, so that its effectiveness can be reduced and tends to be formal. To overcome this, the principal applies efficient time management, delegates some administrative tasks, creates a structured supervision schedule, improves competency through training, workshops, and professional learning communities, and utilizes simple technology for remote supervision, so that supervision remains effective, collaborative, and sustainable despite these limitations.